Topological differentiation of plant communities of the Eastern regions of Ukraine in the Steppe zone (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Question: What is the pattern of distribution of plant communities for the study districts? What research methods should be used to assess the topological differentiation of habitats? Locations: Siversko-Donets and Donetsk forest-steppe geobotanical districts, Ukraine. Methods: critical analysis of the literature sources and electronic resources, ecological and cenotic profiling. Nomenclature: POWO (https://powo.science.kew.org), Mucina et al. 2016, Dubyna et al. 2021 Results: We reflected specificity of the plant communities distribution within the landscapes depending on the ecological conditions in the eastern part of Ukraine in the Steppe zone. There are a lot of mesic deciduous forests exclaves within the Donetsk forest-steppe geobotanical district, which are common in beams, ravines, and partly on the planes. The diversity of forest communities is widely represented, from overmoistened (Alnion glutinosae) to dry (Quercetea pubescentis). Meanwhile there are a wide range of chalk outcrops communities and localities of the chalk pines in Siversko-Donets district. And the meadow vegetation in the study area is characterized by a higher degree of salinity than in the forest-steppe zone. Edaphic factors have a significant influence on the vegetation cover differentiation, on the other hand, the thermoclimate and cryoregime do not have a differentiating value within the landscape. Based on the phytoindication analysis, the inversibility of climatic indicators has been proven. The average annual temperatures and the associated characteristics of the Donetsk forest-steppe district are lower than those of the more northern Siversko-Donets, which is due to the height features of the Donetsk ridge and the nature of its relief.
Keywords: Donetsk forest-steppe geobotanical district, Donets Ridge, Siversko- Donets geobotanical district, landscape differentiation, vegetation